2005
DOI: 10.5194/nhess-5-345-2005
|View full text |Cite
|
Sign up to set email alerts
|

Public perception of flood risks, flood forecasting and mitigation

Abstract: Abstract.A multidisciplinary and integrated approach to the flood mitigation decision making process should provide the best response of society in a flood hazard situation including preparation works and post hazard mitigation. In Slovenia, there is a great lack of data on social aspects and public response to flood mitigation measures and information management. In this paper, two studies of flood perception in the Slovenian town Celje are represented. During its history, Celje was often exposed to floods, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
130
2
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(146 citation statements)
references
References 8 publications
12
130
2
2
Order By: Relevance
“…Comparing these results on perception of flooding vulnerability with similar studies in Slovenia (Brilly and Polic 2005), the Netherlands (Terpstra and Gutteling 2008), Luxembourg (Schaich 2009) and Spain (Lara et al 2010), some strong similarities and differences can be identified. First, experience with risk appears to be a highly determining factor in the perception of the vulnerability of residents living in flood-prone areas.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Comparing these results on perception of flooding vulnerability with similar studies in Slovenia (Brilly and Polic 2005), the Netherlands (Terpstra and Gutteling 2008), Luxembourg (Schaich 2009) and Spain (Lara et al 2010), some strong similarities and differences can be identified. First, experience with risk appears to be a highly determining factor in the perception of the vulnerability of residents living in flood-prone areas.…”
Section: Discussionmentioning
confidence: 73%
“…These multidisciplinary studies have ranged from topics such as: identification of factors that influence the decision of the community to cooperate in disaster management (Brilly and Polic 2005;Howgate and Kenyon 2009;Lara et al 2010;Martin 2010;Das 2011); development of social resilience capacity (Bahadur et al 2010;Norris 2011;Sok et al 2011;Ashley et al 2012;Bakker et al 2012); or aspects of uncertainty linked to climate change, where participatory approaches with different stakeholders are working together to develop a common strategy by managing water resources and urbanization (Ribarova et al 2011;Burch et al 2010;White et al 2010;Samuels et al 2010;Lomas and Giridharan 2011). These studies have contributed to the development of government approaches that lead to the implementation of participatory and inclusive public policies.…”
Section: Introductionmentioning
confidence: 99%
“…This approach can solve problems with population growth, urbanisation and climate change which represent significant pressures on sustainable urban development, requiring flood events managers to consider a wider array of management options that account for economic, social and environmental factors using modeling in GIS environment [25][26][27][28][29][30][31]. …”
Section: Resultsmentioning
confidence: 99%
“…One can retain several elements: the role of the collective memory is undeniable. On the one hand, people's experience lead them to develop reflexes against the warning, but on the other hand, people who have experienced a flood tend to underestimate the danger (Gardner and Stern, 1996;Brilly and Polic, 2005).…”
Section: An Inefficient Warning Systemmentioning
confidence: 99%